Antiquities a Contract Insurance Athlete - Ghelan, Hawraa; Abdulsahib, Ali (Journal of Legal Sciences, 2026)
It is considered a contract Insurance athlete mechanism Legal Tool Tax To protect athletes and others and the audience from Damages that Caused by Risks Sports , Van Accordingly becomes from right The victim claim The believer In compensation when what Available in a contract Insurance athlete The pillars and conditions Private To him , and on him Aims a contract Insurance athlete to events antiquities legal , that is Find situation new Arrange rights and obligations did not bear it And did not earn it Contractors from before , since Arrange a contract Insurance athlete Obligations on Shoulder My side The contract And represented by in Obligations The believer for him from side and obligations The believer from side Other , and it is represented Commitment Main For the believer for him in a contract Insurance athlete he to push Installments For the believer while It is represented Commitment Main For the believer in a contract Insurance athlete he to push amount Insurance athlete in condition verification danger The believer From him